How does climate exacerbate root causes of conflict in Mali? An impact pathway analysis - Madurga Lopez, Ignacio M.; Dutta Gupta, Tanaya; Läderach, Peter R.D.; Pacillo, Grazia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This factsheet gives answers on how climate exacerbates root causes of conflict in Mali, using an impact pathway analysis. Three main impact pathways are identified: 1) Resource availability and livelihood insecurity ; 2) Farmer-herder conflict; 3)Mobility and resource competition in the South.